Performance of initial public offerings: Does shariah compliance extensiveness make a difference? - Zunaidah, Sulong; Mohd Rahim, Ariffin; Nor Azizan, Che Embi (2017)
Despite the popularity and the claim that Shariah companies fare better than their conventional counterparts, both previous studies and market reports show that the Shariahcompliant status does not seem to contribute positively to the Shariah IPO initial performance. This study hypothesizes that this could be due to (i) the characteristic differences between the Shariah IPOs and theirconventional counterparts and (ii) the inadequacy of pre-revision Shariah screening methodology since establishment in 1995 to 2013, in which neglects two crucial financial ratios, debt and ARTA (account receivable to total asset), which are emphasised by the Fiqhi Council. Thus, this study is conducted with the objectives: (i) to ascertain the impact of Shariah extensiveness on the IPO initial performance; and if this is so, (ii) to what extent the Shariah status and level of compliance influence initial performance. This study employs a sample of 153Shariah IPOs issued by Malaysian companies from January 2005 until December 2014. Consistent with past studies, the results show that there are no significant difference between the initial performance of Shariah and non-Shariah IPOs, even after controlling for the IPO characteristics. However, when the level of extensiveness is taken into consideration, the difference in the initial returns prevails.Overall, this study contributes by providing evidence that the existing Shariah screening criteria should incorporates the two financial ratios (debt and ARTA) in order to distinguish the Shariah IPOs from their non-Shariah counterpart.